Character Building Through the Seven Habits of Great Indonesian Children: A Qualitative Case Study in Elementary Schools Implementing the Merdeka Curriculum - Ayuna Kurnia Darojah; Ana Fitrotun Nisa; Wachid Pratomo; Kristi Wardani (Papanda Publisher, 2026)
Indonesia's Independent Curriculum emphasizes character development through the Seven Habits of Great Indonesian Children, yet implementation effectiveness in elementary schools remains underexplored. This study analyzed character building through the seven habits program, examining implementation patterns, embedded character values, barriers, and stakeholder perspectives. A qualitative case study design was employed at Sidomukti State Elementary School, involving 35 fifth and sixth-grade students, three teachers, six parents, and three students for in-depth interviews. Data collection utilized questionnaires, semi-structured interviews, and systematic observations conducted between May and June 2025. Data analysis followed Miles et al.'s iterative procedures involving reduction, display, and conclusion drawing with inter-coder reliability exceeding 80%. Implementation varied significantly across habits, with community engagement demonstrating highest consistency (M=32.60) and early waking presenting greatest challenges (M=10.49). Each habit embedded distinct character values including discipline, honesty, spiritual devotion, cooperation, gratitude, and social responsibility. Four primary barriers emerged: insufficient parental capacity, pervasive technology interference disrupting sleep and social engagement, lack of formal curriculum integration, and limited educational resources. Unexpectedly, external accountability structures facilitated rather than undermined self-regulation development. Successful character formation through habit-based interventions requires comprehensive parenting education, formal curriculum integration, and whole-school technology governance policies addressing systemic barriers across multiple ecological levels.